Risk assessment framework for cumulative effects (RAFCE) - Antwi, Effah Kwabena; Boakye-Danquah, John; Owusu-Banahene, Wiafe; Dabros, Anna; Eddy, Ian MS; Silver, Daniel Abraham; Abolina, Evisa; Eddy, Brian; Winder, Richard S. (Frontiers in Environmental Science, 2023)
Introduction: Regional environmental risk assessment is a practical approach to understanding and proactively addressing the cumulative effects of resource development in areas of regional importance. However, regional assessment is methodologically complex, and frameworks to identify and prioritize regional risk issues to guide effective management decisions are lacking. This research develops a risk and impacts-based cumulative effects assessment framework for scoping regional cumulative effects issues to guide present and future project and regional assessment. We operationalized the framework dubbed Risk Assessment Framework for Cumulative Effects (RAFCE) to assess the risks and impacts of proposed mining development in the Ring of Fire region of Northern Ontario, Canada. Methods: Methodologically, we built on existing studies to understand the key valued ecosystem components (VECs) impacted by mining; organized an expert Bowtie Risk Assessment Tool workshop and interviews to identify regional risks and define the VECs impacted by mining; and developed an impact prioritization model that helped quantify and prioritize impacts of mining. Results and Discussion: RAFCE enabled us to: a) identify drivers and impacts of cumulative effects and potential preventive and mitigation measures for effective cumulative effects management and b) describe, quantify, and rank the major impact and components of regional interest. Using RAFCE, we can identify and prioritize impacts that are cross-cutting, multisector‐driven, synergistic, and relevant to a region, visualize and understand the risk management process, identify policy and management issues to prevent risks or mitigate impacts, and ultimately inform resource allocation for effective regional cumulative effects assessment outcomes. RAFCE is suitable for engaging diverse stakeholders in planning for regional cumulative effects assessment.